Sexual knowledge acquisition and retention for individuals with autism. Issue 2 (2nd April 2016) - Pask, Liza; Hughes, Tammy L.; Sutton, Lawrence R.
Abstract : Healthy Relationships & Autism is a developmentally sequenced, manualized intervention intended for children and adolescents with an autism spectrum disorder (ASD). The curriculum is designed to facilitate healthy interpersonal relationships; three modules cover personal hygiene, sexual knowledge, and a variety of productive interpersonal relations. The current study investigates the effectiveness of the strategies used to increase sexual knowledge for individuals with ASD. Specifically, short step-by-step concrete explanations that are paired with visual modeling and repeated practice accompanied by corrective feedback were delivered to six adolescents who showed a wide range of functional abilities. Pre, post, and one month follow-up measures show that the HR curriculum was effective in increasing sexual knowledge acquisition and retention regardless of the child's level of difficulties.